Understanding worldview and creativity: a reflection from an Islamic perspective - Salah, Machouche; Mohd Abbas, Abdul Razak; Bensaid, Benaouda (2022)
In today's world, most educational institutions regard the effort to create a positive educational environment as an incubator for the growth of creativity and new ideas. Because of its practicality and efficiency in satisfying human needs in all dimensions, as well as its capacity to solve issues, creative thinking has been seen as the quickest approach to bring about the good changes needed today to sustain development and advancement in all dimensions of human existence. Understanding the phenomenon of creativity and its origins, as well as developing approaches and methods to enhance its learning, would be a critical first step towards any projected success in this approach. This qualitative research investigated the relationship between worldview and human creativity from an Islamic perspective. The outcomes of this study show that creativity, like other aspects of human nature, is sensitive to the direction and worldview assumptions that a person considers consciously or subconsciously when managing his or her life affair. Furthermore, the study explained how the Qur'an being the source of the Islamic worldview, provides an extraordinary platform for the blossoming of human creativity by venturing into issues such as human nature, psychic, mental, and behavioural elements of man. As a means of analyzing the pertinent data, the researchers have used the content and textual analysis methods.